Is Rural Income Diversity Pro-Growth? Is It Pro-Poor? Evidence from Georgia - Iain Fraser; Junior Davis; Kelvin Balcombe; Dirk Bezemer (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
This paper contributes to the literature on the role of on rural livelihood strategies in rural growth and poverty reduction. It distinguishes between livelihood diversity strategies that contribute to sustainable growth in household incomes, and those that mainly have a 'coping' function. It suggests that typically, the contribution of livelihood diversity to growing household income is through relaxing dependence on credit for access to capital. In this scenario, livelihood diversity would lead to higher technical efficiency in agriculture via investment and thereby to higher household incomes. Survey data from Georgia are introduced and used to test these hypotheses using a Bayesian stochastic frontier approach. The findings are relevant to defining more clearly the scope and aims of policies to stimulate the rural non-farm economy in developing and transition countries.
Keywords: 330; livelihoods analysis; survey data; incomes; efficiency; Bayesian stochastic frontier approach